Doing business with and in Ireland : a case study of Accenture's challenges and strategies in Ireland - Ernie Widianty (2010)
When the group embarked on our business study mission project, Accenture Ireland (AI) was chosen to be the "lens" for the group to gain cultural insights on doing business in Ireland. Two of the key challenges, namely (1) tight talent market and (2) economic slowdown/downturn were identified as our areas of focus. They were chosen not just because of its strong cultural association but also because they were particularly pertinent in the context of the financial crisis. Contrary to our secondary research findings, our primary interviews in Ireland suggested that opportunities exist in times of crisis. In addition, AI was well positioned to capitalise on these opportunities.